C@SiNW/TiO2 core-shell nanoarrays with sandwiched carbon passivation layer as high efficiency photoelectrode for water splitting - Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Shelke, Manjusha V. (Scientific Reports, 2014)
One-dimensional heterostructure nanoarrays are efficiently promising as high performance electrodes for photo electrochemical (PEC) water splitting applications, wherein it is highly desirable for the electrode to have a broad light absorption, efficient charge separation and redox properties as well as defect free surface with high area suitable for fast interfacial charge transfer. We present highly active and unique photoelectrode for solar H-2 production, consisting of silicon nanowires (SiNWs)/TiO2 core-shell structures. SiNWs are passivated to reduce defect sites and protected against oxidation in air or water by forming very thin carbon layer sandwiched between SiNW and TiO2 surfaces. This carbon layer decreases recombination rates and also enhances the interfacial charge transfer between the silicon and TiO2. A systematic investigation of the role of SiNW length and TiO2 thickness on photocurrent reveals enhanced photocurrent density up to 5.97 mA/cm(2) at 1.0 V vs. NHE by using C@SiNW/TiO2 nanoarrays with photo electrochemical efficiency of 1.17%.

Co-catalytic metal oxide nanoparticles decorated silicon/hematite core shell nanowire arrays as efficient photo electrodes for water splitting - Devarapalli, Rami Reddy; Kamaja, Chaitanya Krishna; Shelke, Manjusha V. (ChemistrySelect, 2017)
By looking global energy demands, development of highly efficient stable semiconductor photoelectrodes for photoelectrochemical (PEC) water splitting is highly desirable. Herein, we have fabricated co-catalytic nanoparticles decorated Silicon nanowire (SiNWs)/Hematite(Fe2O3) core sell structures as photo anodes and studied the PEC water oxidation properties. As, Fe2O3 possess weak oxidation kinetics, decoration of NiO and Co3O4 nanoparticles on SiNW/Fe2O3 by hydrothermal method, which acts as co-catalysts to improves the water oxidation reactions. It was found that decoration of Co3O4 nanoparticles enhances the photocurrent up to 2.6 times, whereas for NiO nanoparticles improvement is of 1.5 times when compared to the undecorated electrodes. Along with enhancement of photocurrents, it also shows shift of onset potentials. The effect of the co-catalytic nanoparticles on the enhancement of photocurrent and charge transfer resistance at the interface of electrode-electrolyte have been studied by electrochemical impedance spectroscopy. Further, flat band potentials of the photo electrodes have been measured by using Mott-schottky analysis.
Keywords: Co-catalysts; photo anodes; Photoelectrochemical cell; silicon nanowires; water splitting

Carbon fabric based solar steam generation for waste water treatment - Higgins, M. W.; Rahmaan, Shakeel A. R.; Devarapalli, Rami Reddy; Shelke, Manjusha V.; Jha, Neetu (Solar Energy, 2018)
Decontamination of waste water is one of the most practical techniques to tackle the worldwide clean water shortage. In recent times, solar steam based decontamination of contaminated water has been attested as a potential sustainable strategy to get clean water using renewable resources. Herein, we report the utilization of Carbon fabric and Titanium Nanorods on Carbon Fabric for solar steam based water purification techniques. The performance of Carbon Fabric was tested under different conditions and the results proved that Carbon Fabric has excellent light to heat conversion capabilities in both real and ideal conditions. Owing to the excellent performance of Carbon Fabric, it was used for purification of different types of contaminated water. About 99.9% of salt and 87% of organic contaminants were removed from saline water and organic waste water respectively, using a simple low cost carbon fabric based homemade prototype. We also present the application of Titanium Nanorods on carbon fabric for the efficient removal of dye molecules like Rhodamine B from contaminated water using solar driven interfacial steam generation mechanism.
Keywords: Desalination; Dye degradation; Solar steam; Waste water treatment